Effects of LED light spectrum on the growth and energy use efficiency of eggplant transplants - Yang, Hao; Wang, Ting; Ji, Fang; Zhou, Qing; Wang, Jianfeng (International Journal of Agricultural and Biological Engineering, 2023)
To enhance the transplants’ growth and reduce energy use efficiency, Eggplant (Solanum melongena L.) transplants (cv. Jingqie 21) were cultivated in a plant factory laboratory under different LED light spectrums. The experimental treatments included white plus blue LED lights (R: B=0.5, WB0.5), white LED lights (R: B=0.9, W0.9), white plus red LED lights (R: B=2.7, WR2.7), white plus red plus UV lights (R: B=3.8, WRUV3.8), and red plus blue plus green LED lights (R: B=5.4, RBG5.4). The transplants were grown for 30 d under a light intensity of 250 μmol/m2·s and a photoperiod of 16 h/d. The morphological indicators and biomass accumulation of eggplant transplants were significantly higher in the W0.9 treatment compared to the other experimental treatments. The photosynthetic quantum yield in the W0.9 treatment exhibited an increase of over 22% compared to that in the WR2.7 treatment. The shoot dry weight of the W0.9 treatment reached (381±41) mg/plant and the leaf area was (113.3±8.9) cm2, indicating a higher health index compared to the other treatments. However, there were no significant differences in the net photosynthetic rate of the leaves among all treatments. The energy yield (EY) of the W0.9 treatment was (37.7±1.8) g/kW·h, which was higher than others. Therefore, considering the high quality of transplants and the maximization of energy use efficiency, the LED light spectrum in the eggplant transplants production was recommended to the white LED light with an R: B ratio of 0.9. Keywords: eggplant transplants, LED light spectrum, growth, energy use efficiency DOI: Citation: Yang H, Wang T, Ji F, Zhou Q, Wang J F. Effects of LED light spectrum on the growth and energy use efficiency of eggplant transplants. Int J Agric & Biol Eng, 2023; 16(3): 23–29.